Acetylation of optically transparent cellulose nanopaper for high thermal and moisture resistance in a flexible device substrate. (17th March 2017) - Yagyu, Hitomi; Ifuku, Shinsuku; Nogi, Masaya
Abstract: Optically transparent cellulose nanopaper is a promising candidate for flexible device substrates because it is lightweight, has a smooth surface and high dimensional stability against temperature. However, the moisture and thermal resistance should be improved, while maintaining high transparency for application. In a transparent polymer composite reinforced with cellulose nanofibers, these properties were improved by cellulose acetylation, which were fabricated by starting from acetylated pulps or rinsing acetylated nanofiber film with water. However, these acetylation procedures reduce the transparency of cellulose nanopaper because the hydrophobic nature of acetyl groups produce inhomogeneous aggregations of cellulose nanofibers, which cause light scattering. Therefore, we propose a new procedure of acetylated cellulose nanopaper by rinsing with low polarity solvents such as toluene. The acetylated cellulose nanopaper obtained shows improved moisture and thermal resistance, and maintained optical transparency. The moisture and thermal resistance increase with the degree of acetyl group substitutions. The total transmittance, haze, crystallinity, coefficient of thermal expansions, dielectric constant, and dielectric loss are constant for varying DSs. These findings promote the application of transparent cellulose nanopaper in flexible device substrates.